Modeling future scenarios of sustainable agricultural innovations adoption: an MCE analysis of biodegradable mulch suitability - Madin, Michael Biwalib (My University, 2025)
Whilst agriculture production faces the challenge of feeding a growing population in the midst of global environmental change, farmers adoption of sustainable innovations to help adapt remain limited. Though a key constraint of adopting many innovations is suitability in a given biophysical context under current and future scenarios, there exist scarce studies on how suitability varies across spatial and temporal extent. Prior studies on factors influencing adoption of innovations have also rarely synthesized evidence on direction of effects. This paradox raises critical questions for research in human-environment geography. The aim of this dissertation is to investigate some of these questions, with particular emphasis on assessing the spatial biophysical suitability of biodegradable mulch (BDM) under recent and future scenarios, and direction of effects of adoption factors. The research combines insights from systematic reviews and GIS-based fuzzy multicriteria analysis techniques. The GIS-based model was used to assess the spatial biophysical suitability of BDM across the conterminous USA. The study identified the Plains, Pacific, and Corn Belt regions as high adoption potential sites, where favorable biophysical suitability (59–99% suitable areas) aligns with enabling socioeconomic conditions (e.g., higher net farm incomes and education levels). Overall, the results suggest that if the world takes the path of SSP370 or SSP585 representing higher emissions with limited mitigation, BDM will have increased relevance as an adaptation with potential to replace plastic mulch and enhance crop production in many areas of the U.S. Theoretically, the study sheds light on how sustainable agricultural innovations are not universally applicable but are highly dependent on local conditions and underline the need for place-based strategies. In the end, it is argued that we will risk obscuring and replicating the very mechanisms in which the current level of sustainable innovation adoption is limited if we fail to promote region-specific strategies.
Keywords: Sustainable agriculture; Plastic mulch; Biodegradable mulch; Adoption; Suitability; Future scenarios modeling